Pregnancy-Associated Changes in Pharmacokinetics: A Systematic Review. - Gali Pariente; Tom Leibson; Alexandra Carls; Thomasin Adams-Webber; Shinya Ito; Gideon Koren (PLoS Medicine, 2016)
Background Women are commonly prescribed a variety of medications during pregnancy. As most organ systems are affected by the substantial anatomical and physiological changes that occur during pregnancy, it is expected that pharmacokinetics (PK) (absorption, distribution, metabolism, and excretion of drugs) would also be affected in ways that may necessitate changes in dosing schedules. The objective of this study was to systematically identify existing clinically relevant evidence on PK changes during pregnancy. Methods and findings Systematic searches were conducted in MEDLINE (Ovid), Embase (Ovid), Cochrane Central Register of Controlled Trials (Ovid), and Web of Science (Thomson Reuters), from database inception to August 31, 2015. An update of the search from September 1, 2015, to May 20, 2016, was performed, and relevant data were added to the present review. No language or date restrictions were applied. All publications of clinical PK studies involving a group of pregnant women with a comparison to nonpregnant participants or nonpregnant population data were eligible to be included in this review. A total of 198 studies involving 121 different medications fulfilled the inclusion criteria. In these studies, commonly investigated drug classes included antiretrovirals (54 studies), antiepileptic drugs (27 studies), antibiotics (23 studies), antimalarial drugs (22 studies), and cardiovascular drugs (17 studies). Overall, pregnancy-associated changes in PK parameters were often observed as consistent findings among many studies, particularly enhanced drug elimination and decreased exposure to total drugs (bound and unbound to plasma proteins) at a given dose. However, associated alterations in clinical responses and outcomes, or lack thereof, remain largely unknown. Conclusion This systematic review of pregnancy-associated PK changes identifies a significant gap between the accumulating knowledge of PK changes in pregnant women and our understanding of their clinical impact for both mother and fetus. It is essential for clinicians to be aware of these unique pregnancy-related changes in PK, and to critically examine their clinical implications.